Effect of relative tool sharpness on subsurface damage and material recovery in nanometric cutting of mono-crystalline silicon: A molecular dynamics approach. (15th March 2020) - Ameli Kalkhoran, Seyed Nader; Vahdati, Mehrdad; Yan, Jiwang
Abstract: Depth of cut (h0 ) and tool edge radius (re ) are two key parameters in nanometric cutting, investigating both of the two parameters simultaneously can provide comprehensive understanding of the cutting mechanism. In this paper, relative tool sharpness (RTS), which is quantified as h0 /re, is employed as a factor to examine the subsurface damage and material recovery in nanometric cutting of mono-crystalline silicon using molecular dynamics (MD) simulation. Various RTS values were generated by changes of cutting depth at different tool edge radius of 1, 3 and 5 nm respectively. Results indicate that there is always a layer of particles which sticks on the tool surface and influences the machined surface, even at RTS = 0. Besides that, the increase of RTS results in subsurface damage layer serration, which is caused by stick-slip phenomenon between the tool and workpiece. A bigger RTS causes a bigger depth of serrations, although the number of serrations remains constant. Increase in RTS also causes the formation of the hexagonal diamond structure. The material recovery drops dramatically by RTS increase. Using a sharper tool edge (RTS<0.25) at a cutting depths below 1 nm does not necessarily decrease subsurface damage due to the drastic stress concentration. It is also demonstrated that silicon amorphisation can occur in the unmachined region in front of the tool due to the hydrostatic pressure wave caused by tool advancement. Graphical abstract: Image 1